Przekształcenia polityki regionalnej Polski pod wpływem zachodzących procesów integracyjnych (unionizacja polityki regionalnej) - Korenik, Stanisław (Transition of Polish regional policy and European community (unionization of regional policy), 2006)
Regional policy as a part of contemporary economic policy is a relatively new field. At the beginning of 21s1 century regional policy is an integral and very important element of economic policy managed by states and international institutions. Character and features of regional policy are determined among others through economic doctrines and government programmes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 79-86